Content of heavy metals (Ni, Cd, Pb) in skin lightening products and dermal health risk among young adult women - Rusmadi, Siti Zulaikha (2016)
Background: Human exposure to heavy metals occurs on daily basis mainly via ingestion of contaminated food sources or inhalation of resuspended dust. Other less obvious sources of dermal exposure includes heavy metal from beauty products. Indeed, heavy metal can be detected in most of beauty products in the form of impurities. The issue of the heavy metals appears as impurities in beauty products was not widely discussed. As skin lightening is the most popular beauty products in certain countries, the presence of heavy metal impurities in it can lead to direct exposure to a large number of individuals. Objective: The aim of this study was to determine the heavy metals concentration in skin lightening product namely facial moisturizing cream and to assess the risk from dermal exposure of its continued application. Additionally, this study attempts to determine the practice, knowledge and perception toward the use of skin lightening among female universities students in Malaysia. Information on perceived skin problem caused by the use of skin lightening was collected. Methodology: This is a cross-sectional study that involved 198 female students which took place in Universiti Putra Malaysia (UPM) and International Islamic University Malaysia (IIUM) from November 2014 to April 2015. Questionnaire was used to determine students’ practice, knowledge and perception on skin lightening. This study sampled 33 skin lightening creams (17 local brands and 16 non-local brands) available in the local market. Samples were digested and tested for heavy metals which are nickel (Ni), cadmium (Cd) and lead (Pb) by using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The physicochemical properties including moisture content, pH, type of emulsion and spreadability were measured. The health risk assessment from continued application was assessed by using Margin of Safety (MoS) and Hazard Quotient (HQ). This study has obtained ethical approval from the Ethics Committee for Research involving Human Subjects of Universiti Putra Malaysia (JKEUPM) prior conducting the study. Result: A total of 117 (59.7%) respondents aged between 20 to 30 years are currently using skin lightening products. Most of the respondents aware that skin lightening might cause health effect (87.8%, N=172). Most of the respondents have the perception that lighter skin provides high self-esteem (54.6%, N=107). The most common skin problems experienced were skin peeling (54.5%, N=22). The concentration of Ni, Cd and Pb in non-local samples was higher compared to local samples with average (standard deviation) of 0.207±0.15 mg/kg, 0.018±0.02 mg/kg and 0.107±0.08 mg/kg respectively. The range MoS of heavy metals in this study was higher than 100 suggesting that the presence of heavy metals impurities in the skin lightening samples were within an acceptable risk to human health. The MoS for Ni was 4.0×107 to 1.1×108, 1.8×105 to 4.1×105 for Cd and 1.8×104 to 8.4×104 for Pb. The HQ for Ni and Cd were less than 1, whereas HQ for Pb was greater than 1 indicating that a potential may exist for adverse health effects. Conclusion: Heavy metals impurities detected in the samples studied were at low concentration and within acceptable risk to human except for Pb. However, care should be taken as metals are able to accumulate in human body and the health effects from it remained concern